Konsumsi Produk Sustainable Beauty di Masa Pandemi: Menjaga Kesadaran Ekologis ataukah Menjaga Fenomena FOMO (Fear of Missing Out)? - Genta Mahardhika Rozalinna; Anastasya Carollita Lukman (Brawijaya Journal of Social Science, 2022)
ABSTRACTThis study aims to analyze the shift in knowledge about the use of beauty products during the global Covid-19 pandemic from conventional products to sustainable beauty products. Conventional beauty products are products that are considered to have environmentally unfriendly packaging such as plastic, contain synthetic chemicals that have the potential to harm the skin and the environment, usually made from palm oil derivatives. Meanwhile, sustainable beauty products are products that are packaged as environmentally friendly (can be recycled) and do not contain synthetic chemicals that can harm the environment. The data collection method used in-depth interviews with five informants consisting of three women and two men with criteria as users of sustainable beauty products both before and during the pandemic, as well as the use of journals and information from related news channels. The result is a shift in knowledge about the use of conventional products to sustainable beauty products, which are more likely to be done by women from the Z generation group (age range 9-24 years). These women understand that the use of sustainable beauty products is very important to protect the environment which is part of maintaining ecological awareness. But on the other hand, all informants did not reject the phenomenon of fear of missing out (FOMO) through the Tiktok platform which was introduced by beauty bloggers regarding the introduction of sustainable beauty products. The FOMO phenomenon is a condition in which a person feels anxious, restless, and afraid of missing the moment experienced by others while he or she is not involved in it. Apart from the increase in skincare products during the pandemic, the FOMO phenomenon has become a marker for purchasing sustainable beauty products as part of self-awareness not only to increase prestige but also to take care of the environment.